PENGARUH AKTIVITAS MENDONGENG TERHADAP KECERDASAN LINGUISTIK DAN EMOSIONAL ANAK - Rani Fardani (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2023)
This research aims to add knowledge about the effect of storytelling activities on children’s linguistic intelligence and emotional intelligence which can provide benefits for educators, writers, parents, observers of children and all parties who focus on literature and children’s issues. The method of this study was library research using various literature reviews with data collecting techniques through the utilization of written sources relevant to the research. Based on the result of the literature rewiew that has been studied deeply, the researcher found the concepts and effects of storytelling that are adapted to the stages of children’s linguistic development and the stages of children’s emotional development so that the effects of storytelling activities can stick until the children become adults later and can be applied in daily life. In terms of linguistic intelligence, storytelling activities must be adapted to the stages of children’s language development including: (1) sensory-motor: introducing storytelling activities use daily simple language, the fairy tale objects displayed that close to daily life, for example: fairy tales about cats and chickens, (2)pre-operational: the language used is further increased in quantity and can be assisted with supporting tools such as fairy tale books with interesting and colorful forms and writing, for example the fairy tale about Malin Kundang, (3)concrete: language that used more complex with a fairy tale content that has a life value that can be discussed with children. Meanwhile, for emotional intelligence, storytelling activities are adapted to the stages of children’s emotional development which contains character traits in terms of: how to recognize their emotions, manage their emotions, motivate themselves, empathize and socialize